2019
DOI: 10.5114/aoms.2018.78776
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of folate concentration in amniotic fluid and maternal and umbilical cord blood during labor

Abstract: IntroductionFolate is required for fetal, placental and maternal tissue growth during pregnancy. A decline in maternal circulating folate concentrations and an increase in total homocysteine (a non-specific indicator of folate deficiency) have been observed with the progression of pregnancy. However, the role of folate in the third trimester of pregnancy is not clear and folate status in late pregnancy has not so far been widely analyzed. The main aim of this retrospective cross-sectional study was to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Folate-a water-soluble vitamin B found in fruits, legumes, cereals, and green leafy vegetables-is required for placental tissue growth [10] and neural tube formation [11]. More recently, its role as a methyl donor in several molecular pathways and epigenetic mechanisms has been demonstrated [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Folate-a water-soluble vitamin B found in fruits, legumes, cereals, and green leafy vegetables-is required for placental tissue growth [10] and neural tube formation [11]. More recently, its role as a methyl donor in several molecular pathways and epigenetic mechanisms has been demonstrated [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The levels of study elements and folate in AF and MS in groups with abnormalities were compared with healthy deliveries as previously published [ 21 , 23 ]. The control group consisted of healthy women without birth defects or any chronic diseases such as diabetes and hypertension, not smoking, without alcohol abuse and preterm birth.…”
Section: Resultsmentioning
confidence: 99%
“…This essential mineral is necessary for the growth of the body and plays an important role in the metabolism of the fetus. Its deficiency in pregnancy may increase the risk of health disorders for both the mother and the newborn, such as mortality and morbidity, gestational diabetes, preterm labor, preeclampsia, and small for gestational age or intrauterine growth restriction [ 21 , 25 ]. It is suggested that the influence of Mg on early development relates to the TRPM7 and TRPM6 ion channels that have been implicated in the control of the homeostasis of Mg ions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations